ICU, hospital and one year mortality of patients suffering from solid or haematological malignancies (Swiss Medical Weekly, 2013)
OBJECTIVE: To examine the demographics, evolution and outcome of patients suffering from malignancies admitted to a medical intensive care unit. PATIENTS AND METHODS: Single centre retrospective cohort study of patients with malignancies. Data on demographics, diagnosis laboratory tests, provided therapy and outcome were retrospectively collected. Data was analysed for differences between patients suffering from solid compared to haematological malignancies as well as for predictors of one year survival. RESULTS: A total of 74 consecutive patients with a median age of 62 years were enrolled. From these, 42 (57%) suffered from solid and 32 (43%) from haematological malignancies. In total, 64% of patients with solid malignancies presented with metastatic disease. The main reason for intensive care unit admission in patients with solid malignancies was acute cardiovascular failure (39%) and infections in patients with haematological malignancies (38%). Intensive care unit mortality, hospital mortality and one year mortality were 26%, 35% and 71% overall; 17%, 29% and 69% respectively in patients with solid and 38%, 44% and 73% respectively in patients with haematological malignancies. Survival was close to 40% in patients with no or one organ failure. Survival dropped to 20% with 2 and 13% with ≥3 organs in failure. The number of organs in failure predicted hospital fatality with an AUCRoc of 0.87. CONCLUSION: The number of failing organs rather than malignancy itself drives outcome even in patients with malignancies. Thus the number of organs in failure rather than diagnosis should guide intensive care unit management in patients with malignancies.